Thermogenic substances: irrational use and the role of the pharmacist (Research, Society and Development, 2023)
For some time now, there has been an abusive increase in the consumption of nutritional supplements and drugs, which induce greater thermogenic action. The indiscriminate use of these products, without knowledge of their effects and their action, can compromise the quality of life of the individual, and may cause harm to health. The objective of the study was to verify through the literature the profile of the user who makes indiscriminate use of thermogenics, report risks associated with this practice, describe the socioeconomic profile of the users and identify the side effects of these individuals. This was a literature review study. The search for evidence was carried out in national and international databases: Scielo, PubMed and Google Scholar. We chose to select only field research articles, carried out in human beings, that indicated the socioeconomic profile, the reason for using supplements and their indication, and review articles in the period from 2010 to 2020. 18 articles were used, in which a great demand of users of these products was observed, in 9 studies a higher percentage of indication by unprepared people was reported and, in only one study, a higher rate of consumption of these supplements was reported by qualified professionals. In this way, it was possible to conclude from the research contained in this review that there was a high prevalence of individuals who use thermogenics indiscriminately, in addition to their association with various side effects such as insomnia, aggressiveness, headache and, among them, cardiovascular diseases.